2021
DOI: 10.3390/pharmaceutics13060820
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Lactobacillus Biosurfactants on Skin Permeation of Hydrocortisone

Abstract: One of the most widely used strategies to improve drug diffusion through the skin is the use of permeation enhancers. The aim of this work was to investigate the effect of two biosurfactants (BS), produced by Lactobacillus crispatus BC1 and Lactobacillus gasseri BC9, on the skin permeation profile of hydrocortisone (HC, model drug). HC aqueous solubility and in vitro diffusion studies through porcine skin were performed in the presence of BC1-BS and BC9-BS at concentrations below and above critical micellar co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 54 publications
2
3
0
Order By: Relevance
“…When BC9-BS was solubilized at concentrations from 0.0625 mg/mL to 8.005 mg/mL, a decrease in surface tension from 66 ± 0.5 to 43 ± 1 dyne/cm was observed and the CMC was found to be around 2 mg/mL. Data obtained are in agreement with our previously published results: the presence of electrolytes allows for a greater reduction in surface tension with respect to water, without affecting the CMC value [ 18 ]. Regarding CAPB, it was demonstrated to reduce surface tension from 67.8 ± 0.3 to 34 ± 0 dyne/cm in the concentration range of 0.005–5.275 mg/mL and it exhibited a CMC value of 1.01 mg/mL, which is in line with what has been already reported in literature [ 27 ].…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…When BC9-BS was solubilized at concentrations from 0.0625 mg/mL to 8.005 mg/mL, a decrease in surface tension from 66 ± 0.5 to 43 ± 1 dyne/cm was observed and the CMC was found to be around 2 mg/mL. Data obtained are in agreement with our previously published results: the presence of electrolytes allows for a greater reduction in surface tension with respect to water, without affecting the CMC value [ 18 ]. Regarding CAPB, it was demonstrated to reduce surface tension from 67.8 ± 0.3 to 34 ± 0 dyne/cm in the concentration range of 0.005–5.275 mg/mL and it exhibited a CMC value of 1.01 mg/mL, which is in line with what has been already reported in literature [ 27 ].…”
Section: Resultssupporting
confidence: 91%
“…Such an increment was even more noticeable when surfactants were used at a concentration five-fold the CMC, reasonably because of amphiphilic molecules tendency to self-assemble in micelles, which are characterized by a hydrophobic region available for the solubilization of HC. BC9-BS, in particular, led to an increase in HC solubility up to 0.300 ± 0.001 mg/mL and 0.357 ± 0.011 mg/mL below and above its CMC respectively, confirming our previous findings: biosurfactants act as solubilizing agents and are able to interact with the drug both as single molecules (i.e., true supersaturation) and micelles [ 18 , 24 ].…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The integrity of the full-thickness skin was evaluated by measuring the electrical resistance (voltage: 100 mV, frequency: 100 Hz; Agilent 4263B LCR Meter, Microlease, I). Membrane samples with an electrical resistance below 1.57 kΩ/cm 2 were excluded from permeation experiments, in agreement with electrical resistance values recommended in literature [ 71 , 72 ].…”
Section: Methodsmentioning
confidence: 66%
“…At concentrations below the CMC, drug permeation through the skin was improved due to the formation of a superficial lipophilic environment and the interaction between BS and the stratum corneum (SC). When skin hydration tests and differential scanning calorimetry (DSC) analyses were carried out to further investigate the BS interaction with the outermost layer of the skin, the data showed that both BS products may be considered as new promising green excipients for drug permeation enhancement through the skin [ 131 ]. Another study by the same research group explored the potential of the L. gasseri BC9 biosurfactant as a natural excipient to enhance the hydrocortisone solubility and nasal delivery and its mucoadhesive properties at concentrations both below and above the CMC.…”
Section: Utilizing Biosurfactants As Adjuvants In Medicine: Drug Deli...mentioning
confidence: 99%